Actual Evapotranspiration in the High Andean Grasslands: A Comparison of Measurement and Estimation Methods - Ochoa-Sánchez, Ana; Crespo, Patricio; Carrillo-Rojas, Galo; Sucozhañay, Adrián; Célleri, Rolando (Frontiers in Earth Science, 2019)
Actual evapotranspiration (ETa) explains the exchange of water and energy between soil, land surface and atmosphere. Despite its importance, it remains difficult to measure directly. Grasslands represent a widespread ecosystem for which further assessment of the measurement and estimation of ETa is needed. Thus, the objective of this study was to compare measurements and estimations of ETa in a mountain grassland ecosystem made using different approaches. The study was conducted in the Zhurucay Ecohydrological Observatory, located in the high Andes of Ecuador between 3500 and 3900 m a.s.l. The study area is a representative site of the páramo ecosystem, in which the vegetation mainly consists of tussock grasslands. ETa was measured or estimated using the following methods: eddy-covariance (EC), volumetric lysimeters (Lys), water balance (WB), energy balance (EB), the calibrated Penman-Monteith equation (PMCal), and two hydrological models (the Probability Distribution Model (PDM) and the Hydrologiska Byråns Vattenbalansavdelning model (HBV-light)). During one year, precipitation (P) accumulated to 1094 mm while ETa (measured with EC) accumulated to 622 mm (with ETa/P = 0.57). On a daily basis, the EC method measured average ETa rates of 1.7 mm/day. The best daily estimates according to percentage bias (pbias), normalized root mean square error (nRMSE), Pearson’s correlation coefficient (r) and the volumetric coefficient (ve) came from the HBV-light model, followed by the PMCal and the PDM (pbias: -2 to -20 %, nRMSE: 12–15 %, r: 0.7–0.9, and ve: 0.7–0.8). On the other hand, the WB, EB, and Lys estimates showed a poor performance (pbias: -10 to -19 %, nRMSE: 25–93 %, r: -0.4 to 0.5, and ve: -0.5 to 0.7). As the methods used in this study are of different types (hydrological, micrometeorological and analytical), their suitability and applications are discussed in terms of their costs, temporal resolution and accuracy. This study identifies low-cost and easy-to-implement alternatives to EC measurements, such as hydrological models and the calibrated Penman-Monteith equation. This study also allows us to provide an increment of progress on the accurate closure of the water balance in grasslands.